HUBUNGAN PENDAMPINGAN SUAMI DALAM PROSES PERSALINAN DENGAN TINGKAT KECEMASAN IBU BERSALIN DI PUSKESMAS KEMBARAN I - Etika Dewi Cahyaningrum (Viva Medika, 2015)
Perineum rupture is a tear that occurs when the baby is born either spontaneously orwith a tool or action. Based on research Puslitbang years 2009 - 2010 in several provincesin Indonesia found that one in five mothers who have ruptured perineum died (20%).Perineum rupture level is the level of the perineum tear that occurs due to certain reasonsat the time of delivery, especially in primiparous, one reason is the birth weight. Theincidence of perineal rupture in normal labor primipara in Kebumen Hospital hasincreased which in 2010 amounted to 675 cases and in 2011 was 818 cases. The purpose ofthis research was to determine the relationship between birth weight infants with rupture ofthe perineum in normal labor primipara in Kebumen Hospital in 2011. The correlationtype descriptive study using a retrospective approach is data taken with a birth weightinfants perineum rupture in normal deliveries at hospitals primiparous Kebumen year2011, the population in this study were all birth mothers totaled 922 primiparous mother,the sampling technique total sampling, data collection by using master table, with dataanalysis using the chi-square. The results showed no association between birth weightinfants with rupture of the perineum in normal labor primipara in Kebumen Hospital in2011. Key words: birth weight babies, rupture perineum, normal childbirth, primipara